Odpowiedź :
A = <-4;3>
B= <2;5>
A U B = <-4;5>
A п B = <2;3>
A \ B = <-4;2)
B\A = (3;5>
A = (-∞;1)
B= <-5;+∞)
A U B = (-∞;+∞)
A П B = <-5;1)
A \ B = (-∞;-5)
B\A = <1; +∞)
B= <2;5>
A U B = <-4;5>
A п B = <2;3>
A \ B = <-4;2)
B\A = (3;5>
A = (-∞;1)
B= <-5;+∞)
A U B = (-∞;+∞)
A П B = <-5;1)
A \ B = (-∞;-5)
B\A = <1; +∞)
A = (-4;3>
B= (2;5>
A u B = (-4;5>
A n B = (2;3>
A \ B = (-4;2>
B \A = (3;5>
b)
A = (-∞;1)
B= <-5;+∞)
A u B = (-∞;+∞)
A n B = <-5;1)
A \ B = (-∞;-5)
B \A = <1; +∞)
B= (2;5>
A u B = (-4;5>
A n B = (2;3>
A \ B = (-4;2>
B \A = (3;5>
b)
A = (-∞;1)
B= <-5;+∞)
A u B = (-∞;+∞)
A n B = <-5;1)
A \ B = (-∞;-5)
B \A = <1; +∞)